Complex therapy of asthenia and cognitive decline against the background of COVID-19 infection in real clinical practice - Denis I. Moroz; Anna S. Isaeva; Inna A. Lavrinenko; Dmitry V. Semin (LLC "MEDIAFORMAT", 2022)
Asthenia syndrome is an actual problem during the pandemic of a new coronavirus infection (COVID-19) due to the high frequency of occurrence, regardless of the severity of the disease, this condition can develop in all patients who have had COVID-19. The clinical picture of postcovid syndrome is very diverse, but the most common are asthenic disorders, anxiety-depressive disorders and cognitive disorders.